Does It Pay to Bet on Your Favourite to Win? Evidence on Experienced Utility from the 2018 FIFA World Cup Experiment - Lajos Kossuth; Nattavudh Powdthavee; Donna Harris; Nick Chater (Institute of Labor Economics (IZA), 2019)
This paper examined whether people gained significant emotional benefits from not engaging in emotional hedging – betting against the occurrence of desired outcomes. Using the 2018 FIFA World Cup as the setting for a lab-in-the-field experiment, we found substantial reluctance among England supporters to bet against the success of the England football team in the tournament. This decision not to offset a potential loss through hedging did not pay off in people's happiness following an England win. It was, however, associated with a sharp decrease in people's happiness following an England loss. Post-match happiness is relatively more stable among those who chose to hedge or were randomly allocated to hedge. We conclude that people do not hedge enough partly because they tend to overestimate the expected diagnostic cost of betting against their social identity, while underestimate the negative emotional impact from betting on their favourite to win when they did not win.
Keywords: G41; I31; 330; hedging; happiness; social identity; wellbeing; world cup; experienced utility